(untitled) - Statler, Oliver (New York, 1968)
Japanese Inn unrolls the colorful scroll of four turbulent centuries in the history of Hapan. It brings to vivid life the emperor's and bandits, the war-lords and merchants, the actors and artists of the time -- and the famous inn that stood at the crossroads of the fabulous empire they fashioned.